Forecasting Time Series: Trend Function with Wavelet - Monika HADAS-DYDUCH (Communications of International Proceedings, 2020)
The aim of this article is to present the author's combination of the creeping trend method with wavelet analysis. The purpose of merging the above-mentioned methods are short-term prediction of time series - several elements, even though as a rule wavelets are used for series consisting of at least several dozen observations. The applied creeping trend method has been modified in several essential stages. The proposed model is mainly used to predict macroeconomic indicators.
Keywords: wavelets; macroeconomic indicators; prediction; creeping trend.